FOREIGN EXPERIENCES IN USING INNOVATIVE TECHNOLOGIES IN MOTHER LANGUAGE LESSONS OF THE PRIMARY CLASS - Rashidova Mehriya Muzaffarovna (Western European Studies, 2024)
This article describes the use of various innovative technologies in primary school mother tongue classes. In addition, there are opinions about the effectiveness of advanced foreign experiences in the use of these technologies in the educational process.
Keywords: education; reading; speaking; lesson